Affective theory of mind in patients with Parkinson's disease. Issue 4 (20th May 2013) - Poletti, Michele; Vergallo, Andrea; Ulivi, Martina; Sonnoli, Alessandro; Bonuccelli, Ubaldo
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to assess the hypothesis that patients with Parkinson's disease (PD) may have difficulties in tasks of affective theory of mind (ToM; the inference on others' feelings) especially in moderate/advanced PD stages. Difficulties of cognitive ToM have already been described in several previous studies. Methods Affective ToM was assessed with the Reading the Mind in the Eyes task in 35 PD patients and 35 healthy controls. Depression, global cognitive status and executive functioning were also evaluated. Patients were distinguished in early PD and moderate PD according to their scores in the Hoehn and Yahr Staging Scale. Results PD patients had more difficulties with affective ToM than healthy controls, also controlling for other variables that resulted in association with this ability. Early PD patients outperformed moderate PD patients, but this difference did not reach statistical significance when controlling for other variables. Conclusion These findings confirmed that affective ToM may be impaired in PD, but any conclusion can be made on the effect of disease progression on this ability of social cognition. Therefore, longitudinal studies are needed to investigate this potential effect.